Hillslope sediment fence catch efficiencies and particle sorting for post‐fire rain storms. Issue 1 (1st December 2020) - Wilson, Codie; Kampf, Stephanie K.; Wagenbrenner, Joseph W.; MacDonald, Lee H.; Gleason, Hunter
Abstract: Sediment fences are often used to monitor hillslope erosion, but these can underestimate sediment yields due to overtopping of runoff and associated sediment. We modified four sediment fences to collect and measure the runoff and sediment that overtopped the fence in addition to the sediment deposited behind the fence. Specific objectives were to: (1) determine the catch efficiency of sediment fences measuring post‐fire hillslope erosion; (2) assess particle sorting of sand, silt/clay, and organic matter from each hillslope through the sediment fence and subsequent runoff collection barrels; (3) evaluate how catch efficiency and particle size sorting relate to site and rainfall‐runoff event characteristics; and (4) use runoff simulations to estimate sediment fence volumes for future post‐fire monitoring. Catch efficiency ranged from 28 to 100% for events and 38 to 94% per site for the entire sampling season, indicating a relatively large underestimation of sediment yields by sediment fences. Most of the eroded sediment had similar proportions of sand and silt/clay as the hillslope soils, but the sediment behind the fence was significantly enriched in sand while the sediment that overtopped the fence was more strongly enriched in silt/clay. The sediment fences had capacities of 3 m 3 for hillslopes of 0.19–0.43 ha, but simulations of runoff for 2‐ to 100‐year storms indicate that the sediment fences would need a capacity of up to 240 m 3 to store all of the runoff and associated sediment. More accurate measurements of sediment yields with sediment fences require either increasing the storage capacity of the sediment fence(s) to accommodate the expected volume of runoff and sediment, reducing the size of the contributing area, or directly measuring the runoff and sediment that overtop the fence. © 2020 John Wiley & Sons, Ltd. Abstract : Drawing of a hillslope sediment fence and the equipment used to measure the runoff and sediment that overtopped the fence with summaries of observed catch efficiencies and particle sorting.